Program Cerdas (Cegah Risiko Diabetes) Sebagai Upaya Pencegahan Diabetes Melitus Di Desa Wonorejo RT 17, Kecamatan Satui, Kabupaten Tanah Bumbu, Kalimantan Selatan - Nur Laily; Salsabila Hayati; Selvia Selvia; Silvi Lidiawati; Siti Assyifa (Jurnal Ventilator, 2023)
Diabetes Mellitus is a chronic disease that occurs because the pancreas does not produce sufficient insulin or the body is ineffective using insulin. Based on the community diagnosis in the community RT.17 Wonorejo village in 2022, Diabetes Melitus as a priority of health problems that must be interferenced because the percentage of diabetes case mellitus by 3.1%. Alternative troubleshooting Diabetes Mellitus in Wonorejo RT 17 village is with CERDAS program. The CERDAS program consists of the activities of establishing and coaching, citing, and blood sugar examination. The purpose of the CERDAS program is to improve the knowledge of the public about diabetes mellitus and encourage the community to regularly check blood sugar examination. The method of implementing the CERDAS program is a lecture and discussion. The results of the devotion showed by the development of 100% CERDAS cadre knowledge included in either category and 100% CERDAS cadre can perform its duties. The CERDAS cadre is prepared to assist free counseling and examination of free blood supervisors and provide information on diabetes mellitus through the whatsapp group. Community knowledge of Diabetes Mellitus after extension is included with a good category of 57.7% and category less than 42.5%.